Perception and Satisfaction of Sociology Graduates - Basnet, Trishana (INTELLIGENCE Journal of Multidisciplinary Research, 2023)
The main aim of this paper is to identify perception and satisfaction of the sociology graduates of Prithvi Narayan Campus Pokhara, regarding their degree in sociology. It attempts to know the educational background of sociology graduates and reason behind selecting the degree as well. Academic happiness is seen to be one of the most crucial variables influencing students' academic success along with their willingness and drive to continue their education. This will ultimately have an impact on their future careers. The population in this study are the Sociology graduates of Masters Level of Prithvi Narayan Campus, Pokhara who had submitted their thesis in year 2073 and 2074 B.S. after the separation of Sociology and Anthropology departments. Attempt was made to do census among 112 graduates but only 55 responses have been collected for the study. The study was completed through descriptive research design. The data collected were analyzed through presenting it into table and graphs. The sociology graduates perceive sociology degree as quite positive and responsible. The study reveals out that they are satisfied with sociological knowledge but majority shows dissatisfaction with the earning of sociology degree.